Survival and lethal outcomes in Orenburg population of patients with systemic lupus erythematosus - N. V. Lazareva; O. V. Bugrova; N. E. Artemova; K. A. Nagornova (Современная ревматология)
Currently, the prognosis for systemic lupus erythematosus (SLE) has improved significantly, but the relative risk of death in these patients is stillhigher than in the general population. Thrombotic complications are one of the leading causes of death in SLE.   Objective: to analyze the survival rate and structure of lethal outcomes in Orenburg population of patients with SLE, including deaths due to thrombotic complications.   Material and methods. A two-stage study of SLE progression and patient survival was conducted from 2007 to 2022. Clinical signs of the diseasewere analyzed in all patients at baseline (n = 68) and in survivors (n = 50) after 15 years. The median age at the time of enrolment in the study was 35 [29; 45] years, the disease duration – 7.5 [3; 13.5] years. During the second stage, the characteristics of the course of the disease in the survived patients and the causes of death in those who died over 15-year period were determined.   Results and discussion. The 10-, 15- and 20-year survival rates in Orenburg population of patients with SLE reached 98.5, 95.5 and 86.3%, respectively. During this period, 18 (26.5 %) deaths were registered, the median age of the deceased was 48.5 [39; 57] years, and the duration of the disease was 22 [16; 30] years. The most common causes of death were thrombotic complications (n = 14, 78 %) due to antiphospholipid syndrome, lupus nephritis, and arterial hypertension. Less frequently, infectious complications were the cause of death (n = 4, 22 %). Patients with thrombotic complications had a 20-year survival rate of 80.2% that was significantly lower than in the SLE group without thrombosis.   Conclusion. The results obtained allow to consider the presence of thrombotic complications in patients with SLE in Orenburg population as an unfavorable prognostic factor.